Quantitative Action Research on Enhancing French Vocabulary Acquisition: The Efficacy of Flashcard-Based Learning Among Undergraduates - Dayapathirana, Nirmani; Prabodini, Madhara; Poornima, Sewwandi (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
This quantitative action research investigates the effectiveness of a flashcard-based intervention in enhancing French vocabulary acquisition among Sri Lankan undergraduate learners. A sample of 60 beginner and intermediate French students was selected through convenience sampling. The study employed pre-test and post-test design, including a control group, with data analyzed using paired-samples t-tests and ANOVA. Over four weeks, participants engaged in a structured flashcard program incorporating French words, English translations, and visual aids. The results demonstrated a statistically significant improvement in vocabulary knowledge, affirming the efficacy of flashcards as a language-learning tool. The action research approach allowed for iterative refinement of the intervention, ensuring its relevance and applicability in real-world educational settings. Additionally, a positive correlation was identified between students' attitudes towards flashcard use and vocabulary gains. These findings contribute to the ongoing development of practical strategies for vocabulary instruction, with implications for language educators seeking to enhance student outcomes through evidence-based practices.